2016
DOI: 10.1074/jbc.m115.698134
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestins Negatively Regulate the Toll Pathway in Shrimp by Preventing Dorsal Translocation and Inhibiting Dorsal Transcriptional Activity

Abstract: The Toll signaling pathway plays an important role in the innate immunity of Drosophila melanogaster and mammals. The activation and termination of Toll signaling are finely regulated in these animals. Although the primary components of the Toll pathway were identified in shrimp, the functions and regulation of the pathway are seldom studied. We first demonstrated that the Toll signaling pathway plays a central role in host defense against Staphylococcus aureus by regulating expression of antimicrobial peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 51 publications
(51 reference statements)
1
26
0
Order By: Relevance
“…It was also identified as the adaptor protein for clathrin-mediated endocytosis [22, 23]. β-Arrestin1 and 2 were involved in the regulation of shrimp Toll pathway [24]. However, whether β-arrestins participate in the internalization of SRs has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It was also identified as the adaptor protein for clathrin-mediated endocytosis [22, 23]. β-Arrestin1 and 2 were involved in the regulation of shrimp Toll pathway [24]. However, whether β-arrestins participate in the internalization of SRs has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in mammals, βarr1 also recruits tyrosine phosphatase TC45 to Stat1 in the nucleus in response to IFN-gamma stimulation and affects Stat1 phosphorylation35. In shrimp, two β-arrestins (βarr 1 and 2) were identified that regulated the Toll pathway negatively by inhibiting Dorsal translocating into the nucleus40. In the present study, βarr1, but not βarr2, was observed to regulate specifically tyrosine phosphorylation of Stat in shrimp, resulting in decreased AMP expression.…”
Section: Discussionmentioning
confidence: 45%
“…βarrs and Stat were reported in shrimp previously4041. TC45 was first identified in shrimp and submitted to GenBank (no.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations